The beneficial effect of natural antioxidants from olive oil with fig and date palm fruit extracts on biochemical and hematological parameters in rats treated with doxorubicin and γ-radiation - Abdallah H. Fathy; Mohamed A. Bashandy; Samir A.E. Bashandy; Ahmed M. Mansour; Khaled S. Azab (Canadian Science Publishing, 2018)
The goal of this study was to determine the possible beneficial effect of olive oil (7 g/kg) with fig (1 g/kg) and date palm fruit (1 g/kg) extracts (OFD) on the toxicity hazards of doxorubicin (DOX) and (or) γ-radiation. The DOX-treated groups received doses of 2.5 mg/kg body weight via intravenous (IV) injection weekly for four consecutive weeks. Rats in the irradiated groups were exposed to whole-body γ-radiation with fractioned doses of 2 Gy weekly for four consecutive weeks. The OFD-treated groups received two weeks of pretreatment with OFD and daily supplementation via oral gavage during the experimental period. The DOX-treated and (or) irradiated groups showed decreases in the antioxidant parameters (reduced glutathione and nitric oxide) as well as increased lipid peroxidation products. In addition, we observed changes in the lipid profile parameters, lipid risk ratios, and hematological values (erythrocyte (RBC) count, hemoglobin (Hb) concentration, hematocrit (Hct) percentage, platelet count, and total and differential leukocyte (WBC) count) in these groups compared with the control rats. The administration of OFD to DOX-treated and (or) irradiated rats significantly ameliorated the oxidative stress markers, lipid profile, risk ratios, and hematological parameters. In conclusion, OFD could be used synergistically to decrease the negative side effects of chemotherapy and radiotherapy.